Pemberdayaan Desain Interior dan Kreativitas di Masa Pandemi melalui Edukasi Daring Bagi Masyarakat Desa Wonorejo, Gondangrejo, Karanganyar - Badriyah, Siti (Institut Seni Indoensia Surakarta, 2023)
Activities implementation of work programs through community sevice during covid -19 Pandemic is a nem moment. The work program is cattied out through a series of stages that have been prepared with careful consideration. Consideration of the effectiveness and quality of the material transferred in a simple but adaptive map mapping to a pandemic situation. The various impacts of COVID -19 pandemic both in the social, economic and cultural sectors provide concern and caution. The presentation with the video tutorial format is considered appropriate and is realized through a series of stages from pre-production, production and post production online and intensive communication between students and mentoring lecturers. The service activity aims to provide science and technology transfer to reduce the impact of current pandemic, which is oriented to the problem of forming a mindsetfor improving habituation and lifestyle. Stimulating creativity and independence for the people of Wonorejo village, Gondangrejo, Karanganyar.To achieve these goals, flexible methods are used during the pandemic, online methods are used in managing work programs with an interior design approach and the culture of the local community. This methods is carried out considering the current situation and conditions during the COVID-19 pandemic. Limitations in time and quality emprowerment services are packaged with modules and tutorial information through social media. This method is able to cover science and technology studies collectively through online consulting and knowledge sharing services. Clinical methods of consultation and applied learning. The cultural approach is applied to get the habits and cultural background in living in the people of Wonorejo, Gondangrejo, Karanganyar. The results of service are in the form of a contribution in forming a positive mindsets (social constructive) in managing the habit and attitude and culture of healty living arranged according to interior desgn parameters, especially bathrooms.